Ácaros de penas (Acari: Astigmata) em aves não passeriformes do Brasil - Pedroso, Luiz Gustavo de Almeida [UNESP] (2015)
Feather mites are the most diverse fauna of arthropods that permanently lives on birds. These mites are morphologicaly adapted to four different microhabitats on their host feathers, which contributes to their diversity. There is a high specificity between the mites and their bird hosts, especially due to the transmission process that occurs mainly from parents to offspring during the parental care, so that each bird group often hosts a specific feather mite fauna, exposing the parallel evolution between these groups. Despite some isolated cases of parasitism, most feather mites are not true parasites, but are rather considered as ectocommensals. Brazil is one of the richest countries in bird diversity, with more than 1900 species reported; in spite of that, feather mites are known for only about 250 Brazilian birds, and even some bird orders have never have examined for feather mites. The aim of this study is to report the feather mite fauna from non passerine birds in Brazil. Roadkilled birds were washed and the mites which remained in the filter paper were collected under dissecting microscope. Feather mites were also collected from museum skins and from feathers collected from captivity birds. The mites were mounted on microscopic slides for identification using Hoyer‟s medium. In total, 62 bird species in 17 orders had their feather mites analyzed, 32 of which being analyzed for the first time. 139 species of feather mites of 77 genera were recorded, being 48 mites identified to the species level and 10 probably represent new genera. 57 mites species belonged to the superfamily Analgoidea, which occurs mainly on the order Passeriformes and on aquatic birds, while Pterolichoidea, with 82 recorded species, occurs mainly on non passerine, terrestrial birds. The most abundant mite family was Pterolichidae (Pterolichoidea), with 40 species in 9 bird orders, followed by Xolalgidae (Analgoidea) (19 species) and Gabuciniidae ...